2021
DOI: 10.1021/acs.chemrev.1c00046
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of 3D Cell–Hydrogel Interactions: Experiments, Models, and Mechanisms

Abstract: Hydrogels are highly water-swollen molecular networks that are ideal platforms to create tissue mimetics owing to their vast and tunable properties. As such, hydrogels are promising cell-delivery vehicles for applications in tissue engineering and have also emerged as an important base for ex vivo models to study healthy and pathophysiological events in a carefully controlled three-dimensional environment. Cells are readily encapsulated in hydrogels resulting in a plethora of biochemical and mechanical communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(56 citation statements)
references
References 439 publications
(780 reference statements)
0
56
0
Order By: Relevance
“…This result suggested that the GelMA hydrogel may stimulate some signaling involved in stemness regulation but not enough to successfully induce CSCs. Nanoclay addition may induce the ECM organization and reconstruction of CSCs, which may be due to the suitable mechanical environment [55] or the negative charge of the nanoclay allowing the hydrogel to sequester water and divalent cations, conferring space-filling and biomolecule diffusion, [55,56] thus leading to good cell-cell or cell-hydrogel-cell communication within the microenvironment. Among these interactions, the GelMA-nanoclay hydrogel may interact with cell surface proteins, including inte-grin, and generate the differential spatiotemporal activation of tyrosine kinases, inducing the expression of proteins related to cell stemness, such as SHH [29] and LGR5 (Figure 4b,c).…”
Section: Comparison Of Expression Profiles Of Hydrogel-induced Sphere...mentioning
confidence: 99%
“…This result suggested that the GelMA hydrogel may stimulate some signaling involved in stemness regulation but not enough to successfully induce CSCs. Nanoclay addition may induce the ECM organization and reconstruction of CSCs, which may be due to the suitable mechanical environment [55] or the negative charge of the nanoclay allowing the hydrogel to sequester water and divalent cations, conferring space-filling and biomolecule diffusion, [55,56] thus leading to good cell-cell or cell-hydrogel-cell communication within the microenvironment. Among these interactions, the GelMA-nanoclay hydrogel may interact with cell surface proteins, including inte-grin, and generate the differential spatiotemporal activation of tyrosine kinases, inducing the expression of proteins related to cell stemness, such as SHH [29] and LGR5 (Figure 4b,c).…”
Section: Comparison Of Expression Profiles Of Hydrogel-induced Sphere...mentioning
confidence: 99%
“…[ 10 ] Incorporation of cells in the interstitial space between connected microgels, often described as 2.5D culture (as cells are in a 3D scaffold without being fully confined by matrix), addresses important cytocompatibility limitations of bulk encapsulation due to pore sizes (microns‐millimeters) orders of magnitude larger than the mesh size of polymer networks (nanometers). [ 11 ] This interstitial space acts not only as a thoroughfare for nutrient diffusion but also as an important environment for cellular colonization by spreading, growth, and migration, [ 12 ] which can collectively be influenced by chemical, mechanical, and topological cues from the microgel substrate. [ 13 ] Recently, matrices of fibrous granular hydrogels were demonstrated to undergo programmable contraction and cell‐driven reorganization, marking the potential for microgel scaffolds to evolve over time in response to both intrinsic and extrinsic cues.…”
Section: Introductionmentioning
confidence: 99%
“…To date, various organic and inorganic encapsulation materials have been explored, including hydrogels, 7 hydrogel− elastomer hybrids, 8 polydopamine, 9 polyelectrolytes, polyelectrolyte/oxidized carbon nanotube hybrids, 10 silica, 11 and calcium phosphate/carbonate. 12,13 All of them are hydrophilic materials because, on one hand, hydrophilic biocompatible materials have been well studied and can ensure the survival of encapsulated cells/microorganisms; 7 on the other hand, the design of hydrophobic biocompatible encapsulation materials is still challenging. 14 Oleaginous microorganisms capable of using hydrophobic substances have attracted extensive attention in various fields.…”
Section: ■ Introductionmentioning
confidence: 99%